Evaluating The Indonesian Public Response to the Gaza War Since 2023: A Political Opportunity Structures - Aswar, Hasbi; Munzilin, Khairul (Jurnal Hubungan Internasional, 2025)
This study analyzed the public solidarity movement in Indonesia in responding to the Palestinian crisis, especially since Israel’s attack on Gaza in October 2023. Both the Indonesian Government and the public have consistently supported Palestine through various means, including political support and humanitarian assistance. Concerning the public’s role, even though there is an active contribution, these actions are mostly still carried out by Muslim communities only. Apart from that, the actions carried out are still not integrated, resulting in not optimal scale of action and scope. Using a qualitative approach, this study explored the factors influencing the less-than-optimal Indonesian public movement on the Gaza issue by collecting data from various documents and other relevant sources and analyzing them using a political structure theory approach to the study of social movements. This study disclosed that Indonesia has an excellent opportunity to be actively involved in various intensive solidarity actions and to have a global impact in supporting Palestine, given its open political structure, elite support, and the absence of state repression. However, the absence of a solid, cross-organizational national alliance, including Islamic movements that focus more on social and humanitarian issues, exhibits the non-optimal potential for a significant movement from the Indonesian public. This study contributes to enriching discussions about the global solidarity movement for Palestine by drawing on specific theories in social movement studies, particularly in the context of Indonesia, a Muslim-majority country that should play a greater role in advocating for the ongoing Palestinian issue.